2017
DOI: 10.1103/physreve.95.023208
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo approach to calculate ionization dynamics of hot solid-density plasmas within particle-in-cell simulations

Abstract: A physical model based on a Monte Carlo approach is proposed to calculate the ionization dynamics of hot-solid-density plasmas within particle-in-cell (PIC) simulations, and where the impact (collision) ionization (CI), electron-ion recombination (RE), and ionization potential depression (IPD) by surrounding plasmas are taken into consideration self-consistently. When compared with other models, which are applied in the literature for plasmas near thermal equilibrium, the temporal relaxation of ionization dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Besides, the ionization model in LAPINS includes field ionization, collision ionization, electron-ion recombination and ionization potential depression. This model can not only be applied for plasmas near thermal equilibrium, but also can be used in relaxation process of ionization dynamics [34]. After considering the collision effect and ionization effect, our PIC simulations are very close to the real situation.…”
Section: Realistic Simulations Containing Collision and Ionization Ef...mentioning
confidence: 64%
See 1 more Smart Citation
“…Besides, the ionization model in LAPINS includes field ionization, collision ionization, electron-ion recombination and ionization potential depression. This model can not only be applied for plasmas near thermal equilibrium, but also can be used in relaxation process of ionization dynamics [34]. After considering the collision effect and ionization effect, our PIC simulations are very close to the real situation.…”
Section: Realistic Simulations Containing Collision and Ionization Ef...mentioning
confidence: 64%
“…The simulations are carried out with the PIC code LAPINS developed by one of the authors. LAPINS is an implicit PIC code [32] which includes collision [33], ionization [34,35], radiation [36], strong field quantum electrodynamics (QED) [37] and nuclear reaction [38]. Because of the amount of calculation, we decided to use a thin target for simulation and diagnose the terahertz radiation, so as to obtain the CTR distribution of 2D and 3D simulations.…”
Section: Realistic Simulations Containing Collision and Ionization Ef...mentioning
confidence: 99%
“…Last but not least, the process that counteracts ionization is recombination , which is not accounted for in EPOCH and might be important. Recombination is mostly believed not to be important in a few ps after laser-target interaction 22 , but some studies have shown that the absence of that makes a clear difference to the final charge states of ions and to the temporal evolution of ionization 23 , 24 . Recombination of ions can occur via free or bound electrons.…”
Section: Discussionmentioning
confidence: 99%
“…In order to confirm the influence of laser intensity on ionization of carbon species, for both focused and defocused configurations, we carried out 2D numerical simulations using the PIC program LAPINE, 23 which includes both ionization and collision dynamics. 24,25 In the simulations, the laser wavelength was taken as 0.8 lm. The dimensionless maximum amplitude of the laser electric field was taken as a 0 ¼ 5 for the intensity at tight focus and a 0 ¼ 1 for the intensity in the defocused configuration.…”
Section: Particle-in-cell Simulations and Discussionmentioning
confidence: 99%